Impact of Cluster Front Line Demonstrations on Green Gram (MH-421) in Sirsa District of Haryana State - Jakhar, Devender Singh; Kumar, Sunil (Indian Journal of Extension Education, 2021)
Pulses are one of the important food crops globally due to higher protein content. In India, they are also responsible for yielding large financial gains by amounting for a large part of the exports. Cluster frontline demonstrations on moong bean crop covering 110 ha area under variety MH-421 were conducted by Krishi Vigyan Kendra at 110 locations in Sirsa district of Haryana state during four consecutive years viz. 2016 to 2019. The technological gaps were identified in existing crop production technology through farmers meetings and group discussions. The findings showed significantÂ increase in the average yield of demonstrated plot (23.1%) over the farmerâ€™s plot of moong bean crop. Average yield of demonstration plots was recorded higher by 26.90 per cent, 20.50 per cent, 20.00 per cent and 25.00 per cent in years 2016, 2017, 2018 and 2019, respectively. The extension gap was 2.02 q/ha, 1.50 q/ha, 1.50 q/ha and 2.00 q/ha while technology gap was 2.48 q/ha, 3.20 q/ha, 3.00 q/ha and 2.00 q/ha in 2016, 2017, 2018 and 2019 respectively. During these four years yield increase in demonstrations plots expressed as additional income over check plots accounted for Rs. 11300/ha, Rs. 900/ha, Rs. 6200/ha and Rs.14400/ha during various years.Â